"Bide nu æt gode þæt ic Grecisc cunne": Attitudes to Greek and the Greeks in the Anglo-Saxon period - Timofeeva, Olga (Adam Mickiewicz University, 2016)
The Greeks were one of those outgroups to whom the Anglo-Saxons had reasons to look up to, because of the antiquity of their culture and the sanctity of their language, along those of the Hebrews and the Romans. Yet as a language Greek was practically unknown for most of the Anglo-Saxon period and contact with its native speakers and country extremely limited. Nevertheless, references to the Greeks and their language are not uncommon in the Anglo-Saxon sources (both Latin and vernacular), as a little less than 200 occurrences in the Dictionary of Old English (s.v. grecisc) testify. This paper uses these data, supplementing them with searches in the Dictionary of Old English Web Corpus, Brepolis Library of Latin Texts – Series A, monumenta.ch and Medieval Latin from Anglo-Saxon Sources, and analyses lexical and syntactic strategies of the Greek outgroup construction in Anglo-Saxon texts. It looks at lexemes denoting ‘Greek’ and their derivatives in Anglo-Latin and Old English, examines their collocates and gleans information on attitudes towards Greek and the Greeks, and on membership claims indexed by Latin—Greek or English—Greek code-switching, by at the same time trying to establish parallels and influences between the two high registers of the Anglo-Saxon period.
Keywords: Old English; Anglo-Latin; outgroup construction; flagged code-switching; etymology; Greek